ARCHITECTURE OF AN ELECTION-ORIENTED BUSINESS INTELLIGENCE SYSTEM (Journal of Information Systems and Technology Management, 2014)
The election decision-making process is very complex, whether to voters or to political parties. The integration of business intelligence into this process may become one of the key elements that support and improve the election decision-making process. This research paid special attention to the integration of business intelligence into such a process. It is inspired by the IMC model and based on cloud computing. This structural concept offers a definition to the four important levels of decision. These levels take into account the maximum number of factors that may influence the success of an election process.